Mechanism and effects of surface morphology on absorption characteristics in ultrashort pulse laser processing of sapphire - Lye, Celescia Siew Mun (2021)
For ultrashort pulse laser processing of a sapphire wafer, nonlinear absorption of laser energy at sufficiently high laser intensity is essential. This study found that in ultrashort pulse laser processing of a sapphire wafer, its surface morphology can have a significant effect on nonlinear absorption and its threshold. Interestingly, for a single side polished wafer, the orientation of the rough or smooth surface towards or away from the laser source (i.e. if the laser is an incident or exit beam) is a critical parameter on the processing outcomes. The orientation of the grinded rough surface affects the amount of light internally reflected within the material; this has a direct impact on the laser energy absorbed and nonlinear absorption threshold. Indeed, the presence of a grinded rough exit surface increases the possibility of total internal reflection of the laser beam at the exit surface; this traps the laser's energy within the material more efficiently and thus promoting nonlinear absorption. This unique characteristic of having total internal reflection at the rough exit surface can result in laser scribing at both the smooth entry and rough exit surfaces simultaneously. This mechanism can be exploited to improve the laser processing of sapphire sample.